PENGARUH VARIASI KONSENTRASI TWEEN 80 dan SPAN 80 TERHADAP KARAKTERISTIK KRIM EKSTRAK ETANOL DAUN NANGKA - Susanti, Emy; Budiarti, Aqnes; Musyafaah, Maul (Universitas Wahid Hasyim, 2021)
ABSTRACT Jackfruit leaves (Artocarpus heterophyllus) are known to have antioxidant activity and formulated in cream. Span 80 and tween 80 are emulsifiers that are widely used in cream formulations. This study aims to determine the antioxidant activity in cream preparations and the effect of concentrations span 80 and tween 80 on the physical characteristics of the cream.The ethanol extract of jackfruit leaves was made by maceration using 70% ethanol. Jackfruit ethanol extract cream is made in 4 formulas based on variations in the concentration of emulgator span 80; tween 80 that is F1 (3%; 3%), F2 (4%; 4%) and F3 (5%; 5%). The cream tested the physical characteristics of the cream including organoleptic, homogeneity, pH, adhesion, spreadability and viscosity, while antioxidant activity carried out by DPPH (1,1-Diphenyl-2-picrylhidrazyl) method. Data on the physical characteristics of the cream obtained were analyzed using linear regression, the results of organoleptic test and homogeneity were analyzed descriptively, and data from the activity of antioxidant creams were statistically tested using One Way Anova. The results obtained showed variation in concentrations of span 80 and tween 80 affecting the physical characteristics of the cream. Increasing the concentration of span 80 and tween 80 in cream preparations can increase viscosity and adhesion but reduce the spreadability. Antioxidant activity of jackfruit leaf ethanol extract obtained from F1 was 23.17%, F2 37.89% and F3 29.82%, significantly different with F(-) was 6.65%,. Variation in concentrations of span 80 and tween 80 do not affect their antioxidant activity. Keywords: Antioxidant, Jackfruit leaf, DPPH, Cream